Overexpression of TCP8 delays Arabidopsis flowering through a FLOWERING LOCUS C-dependent pathway - Wang, Xiaoyan (BMC Plant Biol, 2019)
BACKGROUND: Flowering is a key process in the life cycle of plants. The transition from vegetative to reproductive growth is thus under sophisticated regulation by endogenous and environmental signals. The plant-specific Teosinte Branched 1/Cycloidea/Proliferating Cell Factors (TCP) family transcription factors are involved in many biological processes, but their roles in regulating flowering have not been totally elucidated. RESULTS: We explored the role of Arabidopsis TCP8 in plant development and, especially, in flowering control. Overexpression of TCP8 significantly delayed flowering under both long-day and short-day conditions and dominant repression by TCP8 led to various growth defects. The upregulation of TCP8 led to more accumulated mRNA level of FLOWERING LOCUS C (FLC), a central floral repressor of Arabidopsis. TCP8 functions in an FLC-dependent manner, as TCP8 overexpression in the flc-6 loss-of-function mutant failed to delay flowering. The vernalization treatment could reverse the late flowering phenotype caused by TCP8 overexpression. CONCLUSIONS: Our results provide evidence for a role of TCP8 in flowering control and add to our knowledge of the molecular basis of TCP8 function.